Conhecimento dos profissionais de saúde: construção e validação de instrumento para prevenção da Leishmaniose Visceral na estratégia de saúde da família - Oliveira, Giselle dos Santos Costa (2016)
The visceral leishmaniasis (VL) is an infectious disease and a zoonosis. It is still considered a public health challenge, due to the frequency and mortality caused on the population. The overall objective is to develop an instrument for prevention of Visceral Leishmaniasis in the context of the Family Health Strategy, analyzing the knowledge of health professionals. The specific objectives are characterizing the profile of health professionals on the Family Health Strategy Program; developing an instrument to assess the interest of Health Professionals in the Family Health Strategy Program (FHS) on measures to prevent visceral leishmaniasis in their community; identifying the influencing factors which come into play when those professionals take actions to prevent visceral leishmaniasis; identifying areas of greatest prevalence of visceral leishmaniasis in Mossoró and evaluating the influence of health professionals’ knowledge on the prevalence of visceral leishmaniasis. It is an exploratory, descriptive and quantitative research which was carried out in 30 Basic Health Centers (BHC) of the Family Health Strategy Program in the urban area in the town of Mossoró-RN. The population were health professionals from the FHSP, and the sample composed by 227 elements. Two questionnaires have been administered, one related to knowledge on VL and the other one for identifying the factors that guide health professionals. Data were expressed on standard average and deviation, minimum, maximum, simple frequencies and percentages obtained through the software Statistical Package for Social Science (SPSS) version 20.0. The instrument was developed and submitted to content validation with application of Kappa Index and Content Validity Index. Then, the instrument was applied to health professionals. Being validated with 20 items, divided into five factors such as the work process, environment, socio-personal difficulties, financing, prevention and control. The instrument is suitable and can be used for research in primary health care regarding to prevention and control of visceral leishmaniasis, particularly in endemic areas. Regarding to the knowledge on VL, it was identified that health professionals know the animals that may be affected, enabling an increase in the identification of cases of this disease (OR: 2.74; IC95%=1.17 – 6.41). Knowing the symptoms of the disease in animals is the key to realize its existence (OR: 2.75; IC95%=1.09 – 6.89). In addition, the fact of knowing prevention is a contributing factor to detect the disease in the regions (OR: 2.38; IC95%=1.07 – 5.31). Regarding the transmission times of the disease, it was most relevant to a greater detection of VL cases (OR: 2.75; IC95%=1.24 – 6.05). In conducting an active search for HVL and Canine Visceral Leishmaniasis (CVL), there is a greater risk of finding positive cases of the disease (OR: 2.57; IC95%=1.13 – 5.61). After the crude analysis of the O.R., the adjusted data revealed that these variables are more important. The health professionals have a limited knowledge about the VL, there are still gaps to be considered, especially on the prevention and control of disease in the researched areas. Thus, requiring an ongoing training and implementation of incisive governmental actions